THE EFFECT OF DIFFERENTIATED INSTRUCTION AND ACHIEVEMENT MOTIVATION ON STUDENTSâ WRITING COMPETENCY - Gualbertus, Endal; Nyoman, padmadewi; Made, Ratminingsih (Jurnal Pendidikan Bahasa Inggris, 2013)
This experimental study aims at investigating the effect of Differentiated Instruction and achievement motivation on studentsâ writing competency of tenth grade students of SMAN 2 Denpasar. The design of this research was 2x2 factorial design. Data of studentsâ writing competency were collected by using an essay type test. Meanwhile, data of studentsâ achievement motivation level were collected by using questionnaire. The acquired data were analyzed statistically by two way ANOVA and Tukey test. This research discovers: 1) there is a significant difference in writing competency between the students taught with Differentiated Instruction and those taught with conventional method, 2) there is no significant difference in writing competency between the students having low achievement motivation taught with different instruction and those taught with conventional method, 3) there is a significant difference in writing competency between the students having high achievement motivation taught with Differentiated Instruction and those taught with conventional method, and 4) there is a significant interaction effect of teaching method (Differentiated Instruction and conventional method) and achievement motivation level (high and low levels) on studentsâ writing competency. Â Keywords: differentiated instruction, achievement motivation, writing competency